Investigating novel variants associated with the isoniazid resistance phenotype in MDR-TB using whole genome sequencing - Sims-Handcock, Jethro Dylan (Stellenbosch : Stellenbosch University, 2023)
Sims-Handcock, Jethro Dylan. 2023. Investigating novel variants associated with the isoniazid resistance phenotype in MDR-TB using whole genome sequencing. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/4632784b-6f08-4ee8-9035-133392bda700